The Stakeholder Approach: A Sustainability Perspective - Clifton, Don (Journal of business ethics, 2011)
This article considers the stakeholder approach (SHA) to organisational management through the lens of what it means for humans to live sustainably on the Earth (that is, for there to be a sustainable world). In particular, the article considers if the SHA, as it is presented in mainstream academic and management literature, is supportive of corporate practices that advance the achievement of a sustainable world. The analysis shows the SHA to have significant failings in this regard when viewed against key sustainable world criteria, with issues of concern evident from the normative core of the SHA through to is practical application in the management setting.